Aloiampelos tenuior var. ernstii, a new orange-flowered variety of rambling aloe (Asphodelaceae subfam. Alooideae) - Smith, Gideon F.; Figueiredo, Estrela; Klopper, Ronell R.; Campbell, Eileen E.; Martin, Kristen (Phytotaxa, 2022)
A red- and several yellow-flowered variants of Aloiampelos tenuior (Asphodelaceae subfam. Alooideae), a species of scrambling aloe, are well known, including in cultivation, and apart from the autonymic variety, at least four others have been given taxonomic recognition at that rank. The yellow-flowered varieties of A. tenuior are predominantly, but not exclusively, based on vegetative characters, while the red-flowered variety is distinguished by its flower colour, as well as vegetative characters. The orange-flowered form of A. tenuior, which is much less common in cultivation than A. tenuior var. tenuior or A. tenuior var. rubriflora, is here described as A. tenuior var. ernstii.